TERMOGÊNICOS: UMA REVISÃO SISTEMÁTICA SOBRE O USO DE ÓLEO DE COCO, ÓLEO DE CÁRTAMO E CLA - Vitória Boelter Hann; Mariana de Souza Martins; Raquel da Luz Dias (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Introduction and objectives: We performed a systematic review, with the aim of identifying the main evidence of the use of coconut oil, safflower oil and conjugated linoleic acid in reducing body fat. Materials and methods: The study included only the results of meta-analyzes, clinical trials, case-control studies and case series conducted in humans, published in the last 10 years. Results: The evidences showed that supplementation with conjugated linoleic acid or safflower oil in addition to promoting thermogenic action, provided changes in anthropometric parameters in most studies, with significant reduction in weight, BMI and body fat. Discussion: The results were more evident in studies that combined supplementation with diet and regular physical exercise, which puts in doubt the action of these supplements. No evidence was found that ensure that coconut oil decrease body fat. Conclusion: Depending on the findings of dubious character of these oils supplementation, the differences in methods used in the studies and the lack of mechanisms involved in the results, it is concluded that this type of supplementation has no effect on body fat reduction, necessitating a greater number of studies that prove their efficiency and safety.